Entrepreneurial Intentions of Students of Non-economic Faculties as a Sign of their Entrepreneurial Attitudes and the Result of the Course on Entrepreneurship - Wioletta KILAR; Tomasz RACHWAL (Communications of International Proceedings, 2021)
The aim of the article is to present the results of a study on students’ willingness to start their own business during or after graduation, and to answer the question to what extent an entrepreneurship course has a positive or negative effect on students’ entrepreneurial intentions. In addition, the objective of the study was to identify external and internal (personal) factors influencing the perceptions of starting a business among the respondents and, among those ready to start a business, to identify the preferred activities in relation to the field of study undertaken. The study covered first-year students of 6 non-economic faculties at the Pedagogical University of Kraków (Poland). They showed a strong initial interest in running a business. However, they were significantly (in the case of students in 4 courses) weakened as a result of the course completion. Interpretation of the data indicates that students in the course become aware of what the responsibility and work of an entrepreneur consists of and become familiar with the practical problems and barriers of running a business. The conclusions formulated from the research undertaken can provide recommendations for decision-makers in the field of education and can thus be applied.
Keywords: Entrepreneurship Education; Entrepreneurial Intentions; Entrepreneurial Attitude; Higher Education